مراعاة حال المتلقي في التقعيد النحوي نماذج من كتاب سيبويه: جمعا ودراسة - مخلوف، إيمان مصطفى محمد عبدالعال (جامعة الأزهر - كلية اصول الدين والدعوة باسيوط, 2019)
نظرا لما لكتاب سيبويه من مفارقات بين مرحلة اللحن المشهورة، وبين تجلية النحو في قواعد وقوالب يسهل الرجوع إليها وللبحث فيما يشكل القاعدة النحوية، سواء أكان تركيبا، أم غيره كالسامع والمتكلم وللكشف عن أسرار ومكنون الكتاب، وترتيب بناء القاعدة على عناصرها الأساسية. ونظرا لبراعة سيبويه في استنتاج وصياغة القاعدة، وتوضيح دور كل عنصر في القاعدة. وعلم النحو يبحث في تقدير الكلمات في الجملة ووضع الحركات المناسبة على أواخرها، وقد بدأ هذا العلم بعد جمع القرآن الكريم، وتشكيله تشكيلا سليما إذ من الثابت أن أول من اقترح تشكيل القرآن وتثبيت الحركات عليه ووضع قواعد وأساسات علم النحو خوفا من الضياع والاندثار، هو يحي بن يعمر قال ابن خلكان (كان لابن سيرين مصحف منقوط نقطة يحي بن يعمر وكان ينطق بالعربية المحضة) وقد اشتهر في اللغة (علماء النحو) كثر كان لهم فضل كبير في وضع أساسات علم النحو، وكانت لهم مؤلفات في هذا المجال، وضمن هذه الكتب التي ذاع صيتها كتاب سيبويه، الذي يعد مرجعا لكل باحث في اللغة العربية، إذ يعد كتاب سيبويه من أهم الكتب اللغوية، وقد وصف بأنه أهم كتب النحو على الإطلاق، ولم يكتب أي كتاب مثله، كما يعد هذا الكتاب علامة فارقة في النحو العربي؛ إذ يحتوي على قواعد غنية ومهمة، وصعبة في بعض الأحيان، وقد أولى العلماء كتاب سيبويه أهمية كبيرة، لما تميز به عن باقي كتب النحو؛ ويعتبر بمثابة الدستور للغة العربية، إذ سلك فيه طريقة خاصة جدا به في تقديم علم النحو، وتطرق إلى عدد من المواضيع ومنها: مباحث النحو، الممنوع من الصرف، النسب، الإضافة والتصغير وغيرها، كما أن هذا الكتاب موسوعة متكاملة تحوي جميع مباحث علم النحو والصرف، إلى جانب المجاز والمعاني وكل ضرورات الشعر، ومباحث الأصول العربية، بالإضافة إلى تعريب اللغة الأعجمية، ويمتاز الكتاب بعدم وجود مقدمة له دون بقية كتب اللغة العربية. وقد قال عنه الجاحظ في أحد كتبه: (لم يكتب الناس في النحو كتابا مثله). فقد برز الكثير من الأسماء في سماء اللغة العربية والنحو العربي، فأطلق عليهم تسمية النحاة، وهم أولئك الذين صبوا جل اهتمامهم على دراسة اللغة وأساليبها وتراكيبها، وعلى رأسهم جميعا إمام النحويين (سيبويه) كما أني لاحظت وجود دراسات سابقة تظهر حال المتلقي مثل (قرينة السياق ودورها في التقعيد النحوي والتوجيه الإعرابي في كتاب سيبويه) وإن كان تناولها من حيث دلالة السياق عامة أما بحثي هذا فمن حيث التقعيد النحوي. ولهذا وغيره كان اختياري لموضوع يتعلق بكتاب سيبويه فهو إمام النحاة وأول من شرح علم النحو وبسطه، وكذلك لاشتماله على جميع قواعد النحو التي تخيرت منها موضوع يتعلق بالسامع وأثره في تقعيد القواعد واعتبرت كتاب سيبويه نموذجا وكانت الخطة العلمية التي سار عليها البحث على النحو التالي: 1- مقدمة: وضحت فيها سبب اختيار لهذا الموضوع والخطة المتبعة في هذا البحث. 2- تمهيد: وعنوانه سيبويه والتقعيد. وضحت فيه. المطلب الأول: كل ما يتعلق بسيبويه من اسم ونشأة وتلاميذ وشيوخ ووفاة. المطلب الثاني: وضحت كل ما يتعلق بكتاب (الكتاب) وبيان قيمته بين كتب النحو. المطلب الثالث: مفهوم المتلقي، والتقعيد من خلال كتب المعاجم. صلب البحث وتناولت فيه الشواهد التي تدل على أثر المتلقي في تقعيد القواعد النحوية مطبقة إياها على نماذج من كتاب سيبويه مرتبة على حسب ورودها في الكتاب على النحو التالي: المبحث الأول: القضايا الموقعية، وقد اشتمل على الآتي: تحريك الساكن للتخفيف الرتبة ترخيم المنادى للتخفيف التوكيد قطع النعت المبحث الثاني: القضايا غير الموقعية، ويشمل الآتي: كثرة الاستعمال حذف العامل أساليب نحوية منوعة ويشمل التمني والتعجب أدوات النداء الخاتمة ووضحت فيها ما توصلت إليه من نتائج. الفهارس الفنية
Due to Sibawayh's book paradoxes between the famous melody phase, and manifestation of grammar in the rules and templates that are easy to refer to and look at what constitutes the grammatical rule, whether installed, or other is like a listener and a speaker, and to reveal the secrets and hidden of the book and the arrangement of the rule based on Its basic elements. Given the ingenuity of Sibawayh in deducing and formulating the rule, it clarifies the role of each element in the rule. The science of grammar looks at the appreciation of words in the sentence and put the appropriate movements at the end, and this science began after the collection of the Quran and formed a formation as it has proven that the first to suggest the formation of the Quran and fixation of movements and the establishment of the rules and foundations of the science for fear from loss and extinction, is Yahia ibn Yemr said Ibn Khalkan (Ibn Sirin had a dotted Koran point Yahya ibn Yomar and was utterly pure Arabic) and has been famous in the language (Grammaologist( many had a great credit in laying the foundations of grammar, and they had books in this area and within these books that have become famous Sibawayh book, which is a reference for every researcher in the Arabic language; Sibawayh book is one of the most important language books, has been described as the most important books of grammar at all, and did not write any book like him, as this book is a milestone in Arabic grammar; The rules are rich and important, and sometimes difficult, and scientists have given the book Sibuyh great importance, for what distinguish it in the presentation Grammar; and is considered as the constitution of the Arabic language, as it has a distinctive way of presenting the science of grammar ،and touched on a number of topics and including: Grammar researches, An unnonated noun, attribution, addition and diminutive and other. This book is also an integrated encyclopedia containing all the topics of grammar and morphology beside meanings, metaphor and all poetry aspects, researches of Arabic assets in addition to translate foreign language to Arabic. In one of his books, al-Jahez said: "People in grammar did not write a book like him." A lot of names have emerged in the sky of Arabic and Arabic grammar, so they have been called the grammarians; and they are those who poured most of their attention on the study of language and methods and structures, and on top of them all Imam Grammar (Sibwayh) As I have noticed the existence of previous studies show the status of the recipient such as and they are those who poured most of their attention on the study of language and methods and structures, and on top of them all Imam Grammar (Sibwayh) As I have noticed the existence of previous studies show the status of the recipient such as (context and its role in the complexity of grammar and Arabic guidance in Sibawayh, book) and That was addressed from the significance of the overall context either research this is where the complexity of grammar. For this and other was optional for a topic related to the Sibawayh's book who was the imam of the grammarian and was the first one who explain the science of grammar and simplified it, as well as to include all the rules of grammar which I chose a topic concerning the listener and its impact on the retention of the rules. Sibawahy's book was I considered a model and the scientific plan followed by the research was as follows: 1- Introduction: I explained the optional reason for this topic and the plan followed in this research. 2- Preamble: its title Sibawayh and complexity. I explained: * The first requirement: Everything related to Sibawayh, his name, arise ،disciples, elders and death. * The second requirement: clarified everything related to the book (AL ketab) and a statement of its value between the books of grammar. * The third requirement: the concept of the recipient, and complexity through the dictionaries books 3- The crux of the research and dealt with the evidence that shows the impact of the recipient in the retention of grammatical rules applied to the models of the book Sibawayh arranged according to their receipt in the book as follows (A) The first topic is on-site issues and has included the following: 1- Stirring Static Dilution 2- Rank 3- Marbling Caller 4- Emphasis 5- Cutting participle (B) The second topic is non-signatory issues and includes the following: 1- Frequent use 2- Delete factor 3- Various grammatical methods and includes wishful thinking and exclamation. 4- Conclusion and clarified the results. 5- Technical indexes. research's subject: taking into account the status of the recipient in grammar complexity Researcher's Name: Dr. Eman Mostafa Mohamed Abd Al Makhlouf
Keywords: التعقيد النحوى -- النحو والصرف -- سيبويه، سيبويه عمرو بن عثمان بن قنبر الحارثي، ت. 796 م